A review of brief cognitive assessment tests. Issue 2 (3rd April 2013) - Slater, Helen; Young, John
Summary: There is a rising prevalence of dementia in line with the continuing demographic transition. More timely diagnosis of dementia is recommended. Brief cognitive tests are useful as they provide a rapid assessment that can indicate the possibility of dementia and identify people for detailed cognitive assessment. Many brief cognitive tests have been developed and practitioners need information in order to select a test that performs well, is acceptable to patients, and is suitable for the relevant care setting. In a structured review, we identified twelve brief cognitive impairment tests, of which six have been sufficiently studied and can be recommended for use in routine care.